2014
DOI: 10.1021/jf405549z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heating Time and Temperature on the Chemical Characteristics of Biochar from Poultry Manure

Abstract: Poultry manure (PM) chars were obtained at different temperatures and charring times. Chemical-physical characterization of the different PM chars was conducted by cross-polarization magic angle spinning (CPMAS) (13)C NMR spectroscopy and thermal analysis. CPMAS (13)C NMR spectra showed that the chemical composition of PM char is dependent on production temperature rather than on production duration. Aromatic and alkyl domains in the PM chars obtained at the lowest temperatures remained unchanged at all heatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 43 publications
10
54
1
2
Order By: Relevance
“…And the results showed a slight difference between SN6 and SN8 while SN8 had a slender lead on adsorption capacity in a given environmental condition. It is generally accepted that increase in pyrolysis temperature may improve the sorption ability of biochars to aqueous nitrate because of the higher aromaticity, weaker polarity and higher specific surface areas [17,18,19]. However, results in this study showed biochars made at a relatively lower temperature (400 ℃) had the strongest adsorption capacity.…”
Section: Effect Of Preparation Conditions On Biochar Adsorption Of Nicontrasting
confidence: 59%
“…And the results showed a slight difference between SN6 and SN8 while SN8 had a slender lead on adsorption capacity in a given environmental condition. It is generally accepted that increase in pyrolysis temperature may improve the sorption ability of biochars to aqueous nitrate because of the higher aromaticity, weaker polarity and higher specific surface areas [17,18,19]. However, results in this study showed biochars made at a relatively lower temperature (400 ℃) had the strongest adsorption capacity.…”
Section: Effect Of Preparation Conditions On Biochar Adsorption Of Nicontrasting
confidence: 59%
“…A maior estabilidade de C no biocarvão é resultante de perdas variáveis de H, O, C e N durante a pirólise, em que se preserva relativamente mais C e, assim, se reduzem as relações H/C, O/C e (O+N)/C (Novak et al, 2009). Essas alterações da pirólise da cama de frango correspondem ao incremento do pico principal de arilas (compostos aromáticos) e redução das alquilas, metilenos e carboidratos (celulose e hemicelulose), em que estes últimos tendem a zero a temperaturas acima de 350 o C. (Cimò et al, 2014).…”
Section: Resultsunclassified
“…With pyrolysis temperature at 650˚C, aliphatic chains, aromatic rings and elemental composition of C, N and O are reduced, making the biochar more recalcitrant [44]. Many characteristics, such as ash content, CEC and C/N ratio, vary according to the raw material [45] and [46], which justifies similar CO 2 emission values for the BCS, whether pyrolyzed at 350˚C or 650˚C.…”
Section: Discussionmentioning
confidence: 97%